Structure and Topology Analysis of Separated Vortex in Forward-Swept Blade - Liang, D.; Li, Y.; Zhou, Z.; Wiśniewski, P.; Dykas, S. (Frontiers in Energy Research, 2021)
Flow separation commonly affects the stability of turbomachines, especially under low-flowrate conditions. Compared with conventional blades, a forward-swept blade is more efficient at high flowrates. However, experiments and numerical simulations show that a forward-swept blade produces an unstable region under low flowrate. In this paper, the topological analysis is used to analyze the structure and size of flow separation in forward swept blades. Three-dimensional structure and formation mechanism of vortices in forward-swept blades are analyzed using the cross-section flow pattern method. For forward-swept blades, flow separation mainly occurs at the blade tip and corner, accompanied by clear velocity fluctuations, the break-up of shed vortices, and diffusion. With decreasing flowrate, the shedding vortices move forward and the speed of vortex annihilation gradually decreases. In addition, the number of singularities in the rotor passage increases with the decrease of flow rate, and the region affected by shedding vortex increases.